Exploring the Implementation of Student-centered Learning in EFL Classrooms: Perspectives from Islamic Secondary-school Teachers in Indonesia - Miftahul Huda; Arif Husein Lubis (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
One notable goal of the 21st-century pedagogy is the encouragement for the students to be the agent of change in their own learning process realized by the implementation of student-centered learning approach (SCL). However, previous literature noted the discrepancy between what they believe in and what they perform in the classroom. Thus, this descriptive qualitative study aims to extend the study from the perspectives of Indonesian Islamic secondary-school EFL teachers, specifically investigating their perceptions on SCL, preferences of using SCL strategies, and challenges in implementing it. Of nine teachers, four teachers were willing to participate purposively based on their background. Data were collected by using a questionnaire and a follow-up interview. After filling in the questionnaire, four teachers were selected to participate in the follow-up interview. Three major findings were obtained. They have been aware of the importance of SCL, although most of their students were still passive. As a result, they preferred to combine the lecture and the student-centered activities like role-play, simulation, cooperative learning, and problem-based learning. However, they did not regularize the facilitation of individual or group presentation. With respect to the challenges, the interview data disclosed that the teachers encountered the limited allocated time to maximize SCL implementation, students’ passivity and self-confidence deterioration leading to limited responses and meaningful communication, and lack of training in implementing SCL-based assessment. This study provides an insight into the reality of SCL implementation in EFL classroom settings from Islamic secondary-school teachers. Recommendations for further studies are also discussed.